ANALISIS PERCEPATAN WAKTU PROYEK KONTRUKSI MENGGUNAKAN METODE TIME COST TRADE OFF (TCTO): (Studi Kasus Pada Pembangunan Gedung Sarana Pemuda Kecamatan Mangunreja Kabupaten Tasikmalaya) - Anggraeni, Riska; Maskur, Atep; Hartati, Gini (Jurnal Ilmiah Teknik Sipil, 2025)
The implementation of project development must be calculated and arranged in such a way, both in terms of time and cost in order to achieve maximum results. Time and cost have a significant effect on the success and failure of the project. The benchmark for project success is usually seen from the short completion time with minimal costs without reducing the quality of quality. The Youth Facilities Building Development Project in Mangunreja District, Tasikmalaya Regency is indicated to have experienced delays in its implementation process. The purpose of this study is to determine the optimal time and cost generated after accelerating working hours (overtime) using the Time Cost Trade Off method, with the alternative of adding 2 working hours (overtime) on structural work that is on the critical path. Data analysis in this study uses Microsoft Project 2013 to determine the critical path. Based on the results of the calculation analysis with time cost trade off with the addition of 2 working hours (overtime) resulting in an optimal time of 127 working days from the normal duration of 150 days, an acceleration of 23 working days was obtained with a project time efficiency of 15% and resulting in an optimum cost of Rp. 5,363,375,369.06 from the normal cost of Rp. 5,448,649,000.00 there is a cost reduction of Rp. 85,273,630.94 with a cost efficiency of 1.56%.